A COMMUNICATIVE APPROACH IN THE METHODOLOGY AND USE OF THE SPECIALTY LANGUAGE - Mamadaliyeva F. A. (Sciental Journals Publishing, 2025)
The development and active use of communication skills is the main aspect in a professional environment. Intensive methods are based on the global presentation of linguistic material, framed in structures or models. The development of grammatical mechanisms is provided from the dialogues of the main course - based on models. The purpose of teaching foreign languages is the practical mastery of spoken language and professional speech.
Keywords: Method, speech, language, approach, communication, process, term, etiquette, competence.